Design and Analysis of BIMD Double Clad MMF -MZI Using Optiwave Simulation - Abdulwahhab, Asmaa Anaam; Mansour, Tahreer S. (Iraqi Journal of Laser, 2021)
This work focused on principle of higher order mode excitation using in- line Double Clad Multi-Mode Mach-Zehnder Interferometer (DC-MM-MZI). The DC-MM-MZI was designed with 50 cm etched MMF. The etching length is 5cm. The tenability of this interferometer was studied using opt grating ver.4.2.2 and optiwave ver. 7 simulator. After removing (25, 35, 45, 55) μm from MMF and immersing this segment of MMF with water bath contained distilled water and ethanol, in addition to, air. Pulsed laser source  centered at 1546.7nm ,pulse width 10ns and peak power 1.33mW was propagated via this interferometer Maximum modes were obtained in case of air surrounded media which are 9800 and 25 um removed cladding layer, with peak power 49.800 mW, FWHM 192 pm, and the transmitted laser was blue shifted with central wavelength λc 1547.193 nm.